Women making war : female Confederate prisoners and Union military justice - Curran, Thomas F. (Southern Illinois University Press, 2020)
"Using St. Louis as its nexus, this book investigates 440 disloyal women who were arrested and imprisoned by the Union army during the Civil War"--